Change of State in Awajun Modification Sentences from Montaguean Model Theory - Bullón Cornejo, Joaquín Antonio (2021)
This descriptive-explicative paper has the objective to analyze some endowment and modification sentences in Awajun through the Montaguean Model Theory. In the first instance, basic aspects of modification actions are defined. Then, aspects, influential in the formation of this type of sentences, are described. These aspects are the high affectedness and accusative morphemes, as well as the semantic papers of agent and patient. After that, some sentences of the corpus are formalized and analyzed through Richard Montague’s 1970 proposal. Finally, we reach the conclusion that Montague’s proposal is perfectly applicable to awajún.